Penggunaan Metode Altman Z-Score Dalam Analisis Risiko Keuangan PT. BTPN Syariah, Tbk. - Harahap, Lily Rahmawati; Wulandari, Shara; Thoyib, Ellys; Effendy, R Y (Universitas muhammadiyah palembang, 2020)
The purpose of writing this article is to find out how the Altman Z-Score discriminant analysis method has a simple role in conducting financial risk analysis. As an object, PT. Bank Tabungan Pensiunan Nasional Syariah (BTPN Syariah), Tbk. Selected by non-random sampling with purposive sampling technique through the website. PT. BTPN Syariah, Tbk. is one of a financial institution that has a role in Indonesia's economy. As an intermediary, PT BTPN Syariah, Tbk. can not avoid risks, both in the form of financial and non-financial risks. To deal with these risks, one important element is to improve its financial performance. One of the depictions of financial performance can be known from the value obtained by using the Altman Z-Score analysis. The data used in this study are secondary in the form of financial statements, which consist of the balance sheet and income statement. The time period taken as data is the period from 2014 to 2018. After each data is obtained and studied then analyzed by using the Altman Z-Score method. So it can be seen what level of risk PT. BTPN Syariah, Tbk. has, whether the low level of risk, grey area, or high level of risk. From the data analysis, it was found that the level of financial risk of PT. BTPN Syariah, Tbk. is in the low-risk level category. In other words, it describes the company that is not bankrupt. This is indicated by the acquisition value of Z-Score > 2.6 which is 5.7438 in 2014, 6.7326 in 2015, 6.9953 in 2016, 8.2041 in 2017, and 7.2012 in 2018.